Library reservation system using face detection / Nik Ruslawati Nik Mustapa and Nur Athikah Fatehah Rosli - Nik Mustapa, Nik Ruslawati; Rosli, Nur Athikah Fatehah (UiTM Cawangan Perlis, 2022)
Today, Covid-19 has completely changed our way of life. The new generation has made people stay at home, instead of going on vacation. The users are not allowed in a close place, especially in a building or room. The library that used to be packed with people reading books, studying, and using the computer is now becoming empty. The room in the library has been limited only to a certain number of people to prevent any dangerous situation regarding the Covid-19 virus to spread. The room needs to be reserved beforehand for the user to use. This situation has become a problem for users as the user’s desired room may be occupied by other users. Thus, Reservation System using face recognition for the library was developed to overcome this situation. In this paper, the researcher will use the Haar Cascade Algorithm to scan the face and MySQL as a database to detect the room and time slot for a reservation. Phyton language and Visual Studio Code were used to develop the system. The limitation of this project is that the face registration took a long time for some users because of the lightning that makes it the system hard to recognize the face. The recommendations for future work are to use a high technology camera to scan the face and construct an admin page because the system does not have an admin page.